2007
DOI: 10.1142/s0217979207044226
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF Gd DOPING IN YBa2Cu3O7-delta ON THE CRITICAL CURRENT DENSITY

Abstract: Gd is successfully embedded into YBa 2 Cu 3 O 7-δ by the solid state reaction. Rietveld refinements show that Gd replaces Cu in the unit cell. By magnetization and resistivity measurements, the effects of Gd -doping in YBCO on the critical current density J c and the critical temperature T c in YBa 2 Cu 3 O 7-δ( YBCO ) have been investigated. J c varies with the applied field and the content of Gd and has a maximum at x = 0.03. The characteristic behavior of J c with varying the Gd content can be explained in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Both studies indicated the enhanced pinning to be due to stress fields induced by lattice mismatch. Xu et al have studied the effects of Gd substitution on Cu sites in YBCO on the critical current density for Gd concentrations between 0 and 20% [2]. They reported a 'zigzag' variation of critical current density with increasing Gd concentration, and found an optimum concentration to be 0.03 in where x is in mole concentration from 0 to 0.2.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies indicated the enhanced pinning to be due to stress fields induced by lattice mismatch. Xu et al have studied the effects of Gd substitution on Cu sites in YBCO on the critical current density for Gd concentrations between 0 and 20% [2]. They reported a 'zigzag' variation of critical current density with increasing Gd concentration, and found an optimum concentration to be 0.03 in where x is in mole concentration from 0 to 0.2.…”
Section: Introductionmentioning
confidence: 99%